THE ANALYSIS OF STOCHASTIC PROCESSES IN UNLOADINGTHE ENERGYWILLOW CUTTINGS FROM THE HOPPER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The paper deals with the theoretical and experimental investigation of the main characteristics of woody crop cuttings unloading from the hopper. To create a variety of automated systems for material feed there is a need to ensure high performance selecting and unloading the material, in particular, it is of vital importance in designing machines for energy willow planting. The analysis of existing theories in mechanics of loose materials motion made it possible to identify the features of unloading the cuttings that narrowed the area of discussion. We will consider two half-planes located at angles to the horizontal plane as a model for hopper in pilot testing. It is analytically and experimentally determined that woody crops cuttings flow occurs according to dry friction laws and inverse-square law and the flow is normal in nature. The statically stable formation and dynamic arches that prevent the uniform and continuous unloading are in evidence. For the theoretical validation of results, we present a set of cuttings as the pseudo liquid that consists of two phases: a discrete phase formed by cuttings and the continuous phase (gaseous medium, air). Each of these phases in terms of the mechanics of multiphase systems is represented as a solid medium with certain characteristics. According to these assumptions, the process unloading of such structure from the hopper can be modelled on the basis of methods of hydrodynamics of multiphase systems. In such a case the field speeds of such pseudo liquid must satisfy the Navier-Stokes equation type. The analytical and empirical analysis of unloading the energy willow cuttings helps to prove theoretically the possibility of enhancing the process of planting till its full automation. As a result, the study gives the theoretical formula that evaluates the velocity of energy willow cuttings flow, the adequacy of which is partially tested in pilot experiments conducted by the authors of the paper in the process of creating the planting machine. Using the received data for further research will make it possible to take into account all the factors involved in unloading and bridging, which is important for examining and improving this process.